Ekstraksi dan Uji Aktivitas Enzim Bromelin Kasar dari Buah Nanas - Dzulqaidah, Intan; Zanuba, Regina Brigita; Alwi, Andi Siti Fatimah; Salsabila, Arista Rizkika Putri; Mursidi, Siswandi; Muliasari, Handa (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
Pineapple (Ananas comosus) is a source of protease enzymes. The protease enzyme present in pineapple is the bromelain enzyme. Bromelain enzymes are widely used in various industrial fields. The purpose of this experiment was to isolate the bromelain enzyme from pineapple plants, to test the activity of the enzyme, and to determine the optimum temperature of the enzyme. Isolation of the bromelain enzyme from pineapple was carried out by precipitating the pineapple fruit filtrate using table salt (NaCl). Then the crude extract of the enzyme obtained was tested on pieces of meat with variations in the testing temperature (room temperature, hot, and cold). The yield of the crude extract of the enzyme obtained from the experiment was 40%. The results of testing the bromelain enzyme activity of pineapple showed that room temperature was the best temperature for the enzyme to tenderize meat compared to hot and cold temperatures.